Middle School Mathematics Teachers’ Perceptions of Culturally Responsive Teaching - Hicks, Stephanie (My University, 2022)
African American students in K-12 classrooms have struggled to achieve at the same level as their Caucasian peers in the mathematics classroom. The achievement gap between African American students and their Caucasian, Hispanic and Asian peers is a concern for administrators, teachers, and parents. Educators are being tasked to examine their pedagogy to determine how tCritical Race Theory; his achievement gap can be narrowed in mathematics. Middle school mathematics teachers who make academic gains with African American students have a specific skill set. The purpose of this interpretive qualitative study was to understand middle school teachers’ perceptions of the role of culturally responsive teaching strategies in teaching mathematics to African American middle school students. A qualitative study was conducted using an interpretive research design. Semi structured interviews were conducted with five middle school mathematics teachers. Key findings in the study revealed that middle school teachers demonstrating success with African American students have key pedagogical and personal characteristics in common. The data from the interviews were analyzed and yielded the following major themes: building on students’ prior experiences, relationships and trust, empathetic and caring teachers, encouraging students to leverage their social capital, and reflection. Results from the qualitative analysis of interview responses showed that math teachers are engaging in a continuous cycle as they attempt to build on students’ prior experiences, create relationships and trust, become empathetic and caring teachers and encourage students to leverage their social capital. Teachers of African American students do all these things while reflecting on each practice and adjusting as they work through the cycle. Keywords: culturally responsive teaching, African American, middle school
Chapter I INTRODUCTION 1 -- Statement of the Problem 5 -- Purpose of the Study 7 -- Significance of the Study 7 -- Conceptual Framework 8 -- Critical Race Theory 8 -- Cultural Wealth Model 9 -- Culturally Responsive Pedagogy 10 -- Culturally Responsive Mathematics Teaching 12 -- Research Design 14 -- Research Questions 14 -- Definition of Terms 14 -- Limitations of the Study 15 -- Summary 16 -- Chapter II REVIEW OF LITERATURE 18 -- Culturally Responsive Teaching 21 -- Teacher Self-Efficacy and Perceptions of Culturally Responsive Teaching 22 -- Pre-Service and Professional Development of Culturally Responsive …………Teaching 23 -- The Role of Culturally Responsive Instruction 26 -- Culturally Responsive Teaching in Urban Settings 28 -- Culturally Responsive Teaching and African American Teachers 30 -- Culturally Responsive Teaching and Mathematics Instruction 32 -- Culturally Responsive Math Teachers 32 -- Mathematics Instruction of African American Students 34 -- Underperformance of African American Students in Mathematics 35 -- Characteristics of Successful African American Males 36 -- Characteristics of Successful African American Female Students 37 -- Successful Math Strategies for Teaching African American Students 39 -- Characteristics of Successful Mathematics Teachers 40 -- Summary 42 -- Chapter III METHODOLOGY 43 -- Research Design 43 -- Research Questions 44 -- Research Site 44 -- Participants 45 -- Consent to Initiate Study 46 -- Consent to Participate in Study 46 -- Interview Procedures 47 -- Researcher-Interviewer 47 -- Data Analysis 49 -- Validity and Trustworthiness 51 -- Memos 51 -- Collecting Rich Data 51 -- Triangulation 51 -- Iterative Questioning 52 -- Respondent Validation 52 -- Summary 52 -- Chapter IV RESULTS 53 -- Data Analysis and Findings 53 -- Brief Profiles of Participants 54 -- Stephen 54 -- Torie 55 -- Tiffany 55 -- Elizabeth 55 -- Nicole 55 -- Themes from Research Question I 55 -- Research Question 1 55 -- Themes from Research Question 2 66 -- Research Question 2 66 -- Summary 69 -- Chapter V 71 -- DISCUSSION AND CONCLUSIONS 71 -- Research Design 71 -- Research Questions 72 -- Discussions 73 -- Building on Students Prior Experiences 74 -- Encouraging Students to Leverage their Cultural Capital 75 -- Relationships and Trust 75 -- Empathetic and Caring Teachers 76 -- Reflective Teachers 77 -- Theoretical and Conceptual Frameworks 78 -- Cultural Community Wealth Model 78 -- Culturally Responsive Mathematics Teaching 82 -- Research Question 1 85 -- Research Question 2 86 -- Limitations of the Study 87 -- Conclusion 87 -- Recommendations 88 -- Appendix A: Participant Consent Form 98 -- Appendix B: IRB Approval 100 -- Appendix C: Informed Consent 102 -- Appendix D: Interview Protocol 105
Keywords: African American students; Culturally relevant pedagogy; Dissertations, Academic--United States; Education; Middle schools; Critical Race Theory